D. Teodósio II, 7º duque de Bragança. Práticas senhoriais como política de reputação - Cunha, Mafalda Soares da (2010)
According to this article, the practices of patronage and sponsorship by the Casa de Bragança should be understood against a larger backdrop of a management meant to safeguard and preserve the ducal house’s signs of preeminence. Its argument is based on two perspectives. According to the first one, the duke’s attitude fits in the global framework of sponsorship practices that the ducal house developed along the 16th and 17th centuries; the second one, on the other hand, is a comparative perspective with other prominent manor houses in Andalusia, where the attitude of the dukes of Bragança fits in the aristocratic patterns of behaviour of the time. This comparison with other major manor houses brings down the exceptional character of the ducal practices.